Leadership style as a predictor of employee commitment in university libraries in South-West, Nigeria. Issue 6 (12th August 2019) - Mayowa-Adebara, Okeoghene; Opeke, Rosaline Oluremi
Abstract : Purpose: The purpose of this paper is to investigate the influence of leadership style (LS) on employee commitment (EC) in university libraries in South-West, Nigeria. Design/methodology/approach: The study adopted a survey research design. The population of the study consisted of 684 librarians from 43 universities in the six states of South-West, Nigeria. A validated questionnaire was used for data collection. Data were analyzed using descriptive and inferential statistics. Findings: Findings showed that the level of EC in university libraries in South-West, Nigeria was fairly high ( M =2.64 on a four-point scale). LS had a significant influence on EC in university libraries in South-West, Nigeria ( β =0.245, R 2 =0.276, p <0.05). However, transformational LS ( β =0.383, p <0.05) relatively contributed more to EC than transactional LS ( β =0.183, p <0.05). Research limitations/implications: A limitation of the study was that the study was done in all the university libraries in South-Western region of Nigeria which may affect the inference of the study results to other university libraries outside this region. Practical implications: The findings of the study will be of benefit to academic institutions, library management and librarians on planning and decision making regarding personnel management. Originality/value: The study therefore recommends that administrators, library managers should adopt transformational LS.